Recombinant human thrombomodulin in the treatment of acute myeloid leukemia patients complicated by disseminated intravascular coagulation: retrospective analysis of outcomes between patients treated with heparin and recombinant human thrombomodulin therapy. Issue 1 (July 2015) - Takezako, Naoki; Sekiguchi, Naohiro; Nagata, Akihisa; Homma, Chiho; Takezako, Yayoi; Noto, Satoshi; Natori, Kazuhiko; Miwa, Akiyoshi
Abstract: Background: Recombinant thrombomodulin (rTM) is a promising anticoagulant. Improvements in disseminated intravascular coagulation (DIC) and the amelioration of bleeding complications in DIC patients were reported to be greater with rTM therapy than with unfractionated heparin therapy. However, it remains unknown whether rTM therapy affects the outcomes of patients with acute myeloblastic leukemia (AML). Design and method: We retrospectively analyzed 103 patients with AML and compared outcomes between patients treated with low molecular weight heparin therapy and rTM. The diagnostic criteria for DIC were previously proposed by the Japanese Ministry of Health and Welfare. Comparisons between qualitative variables were carried out using the χ 2 test. Survival probabilities were estimated by the Kaplan-Meier method, and differences in survival distributions were evaluated using the log-rank test. Results: Forty-seven patients developed DIC due to chemotherapy or their disease status. Fourteen patients were treated with rTM, while 33 patients were treated with low-molecular-weight heparin (LMWH). The log-rank test revealed that overall survival was significantly worse in the DIC group than in the non-DIC group (P = 0.003), and was signfiacntly better in the rTM group than the LMWH group (P = 0.016). Conclusion: rTM was more efficient than LMWH because of the improvements it induced in overall survival. Highlights: Recombinant thrombomodulin (rTM) is a promising anticoagulant agent. It is unknown as to whether or not the treatment with rTM affects AML patient's outcome. We retrospectively analyzed the outcomes between patients treated with low-molecular-weight heparin and rTM.